2015
DOI: 10.3892/or.2015.3870
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant hypomethylation-mediated CD147 overexpression promotes aggressive tumor progression in human prostate cancer

Abstract: Abstract. Our previous study revealed the potential role of CD147 in human prostate cancer (PCa). Here, we investigated the CD147 promoter methylation status and the correlation with tumorigenicity in human PCa. CD147 mRNA and protein expression levels were both significantly higher in the 4 PCa cell lines, than in the 2 non-tumorigenic benign human prostatic epithelial cell lines (all P<0.01). We showed hypomethylation of promoter regions of CD147 in PCa cell lines with significant CD147 expression as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Kong et al recently showed that hypomethylation in a specific CD147/ BSG promoter region, comprising SP1 binding sites, leads to upregulation of CD147 expression and is associated with poor prognosis in HCC [ 15 ]. Liang et al also showed that CD147 hypomethylation is associated with overexpression and tumor progression in prostate cancer [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al recently showed that hypomethylation in a specific CD147/ BSG promoter region, comprising SP1 binding sites, leads to upregulation of CD147 expression and is associated with poor prognosis in HCC [ 15 ]. Liang et al also showed that CD147 hypomethylation is associated with overexpression and tumor progression in prostate cancer [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD147 has a broad tissue distribution, but its overexpression is also seen in breast cancers, HCC, esophageal and cervical squamous cell carcinoma, genitourinary, gastric, colorectal, prostate and ovarian cancers [ 1 , 2 , 17 ]. Liang et al [ 18 ] found that promoter hypomethylation of CD147 might result in the cancer-related overexpression of CD147 because more Sp1 protein bound to its promoter [ 18 , 19 ]. Wang et al [ 20 ] showed that CD147 silencing inhibited cell proliferation, invasion and increased chemosensitivity to cisplatin in SGC7901 cells in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Promotes aggressive tumor progression in human PC (119) TFF1 and TFF3 Their overexpression in PC may serve as biomarkers (120) resistance in GC cells, ubenimex epigenetically inhibits the activation of the CD13/EMP3/PI3K/AKT/NF-κB pathway (154). Additionally, the NFκB pathway participates in the acquisition of resistance to tyrosine kinase inhibitor (TKI) treatment in lung cancer.…”
Section: Cd147mentioning
confidence: 99%